W-Doped TiO2 for photothermocatalytic CO2 reduction. Issue 33 (18th August 2020) - Li, Yingying; Walsh, Andrew G.; Li, Dashuai; Do, David; Ma, He; Wang, Changhua; Zhang, Peng; Zhang, Xintong
Abstract : TiO2 is one of the most widely used photocatalysts and photothermocatalysts. Abstract : TiO2 is one of the most widely used photocatalysts and photothermocatalysts. Tailoring their structure and electronic properties is crucial for the design of high-performance TiO2 catalysts. Herein, we report a strategy to significantly enhance the performance of TiO2 in the photothermocatalytic reduction of CO2 by doping high crystalline nano-TiO2 with tungsten. A variety of tungsten doping concentrations ranging from 2% to 10% were tested and they all showed enhanced catalytic activities. The 4% W-doped TiO2 exhibited the highest activity, which was 3.5 times greater than that of the undoped TiO2 reference. Structural characterization of these W-doped TiO2 catalysts indicated that W was successfully doped into the TiO2 lattice at relatively low dopant concentration. Synchrotron X-ray absorption spectroscopy at both the W L3 - and Ti K-edges was further used to provide insight into the local structure and bonding properties of the catalysts. It was found that the replacement of Ti with W led to the formation of Ti vacancies in order to maintain the charge neutrality. Consequently, dangling oxygen and oxygen vacancies were produced that acted as catalytically active sites for the CO2 reduction. As the W doping concentration increased from 2% to 4%, more such active sites were generated which thus resulted in the enhancement of the catalytic activity. When the W doping concentration was further increased to 10%, the extra W species that cannot replace the Ti in the lattice aggregated to form WO3 . Due to the lower conduction band of WO3, the catalytic O sites were deactivated and CO2 reduction was inhibited. This work presents a useful strategy for the development of highly efficient catalysts for CO2 reduction as well as new insights into the catalytic mechanism in cation-doped TiO2 photothermocatalysis.